Dialectics of International Relations and Religious Tolerance in the Formation of Civil Society (Eurasian Journal of Humanities and Social Sciences, 2022)
The article discusses some issues of integrating religious tolerance and interethnic consent to the minds and the hearts of our people, one of the priorities defined in the "Strategy of Action" in the process of formation and development of civil society restored in Uzbekistan, as well as suggestions and recommendations for its implementation.